Almost Phaseless Sampling for Spline Spaces with Arbitrary Knots*. (18th August 2021) - Li, Rui; Zhang, Qingyue
Abstract: This article deals with almost phaseless sampling for spaces generated by B-splines with arbitrary knots. We provide a necessary and sufficient condition, which is a characterization of an almost phaseless sampling set, to admit phase recovery for almost all B-spline functions on an interval. Our results show that only N + 1 intensity measurements are sufficient to recover phase information for almost all functions in N dimensional B-spline function spaces with arbitrary knots.